Bleeding complications with clopidogrel or ticagrelor in ST-elevation myocardial infarction patients – A real life cohort study of two treatment strategies. (April 2020) - Alfredsson, Joakim; Omar, Kime; Csog, József; Venetsanos, Dimitrios; Janzon, Magnus; Ekstedt, Mattias
Abstract: Introduction: Dual antiplatelet therapy (DAPT), including potent P2Y12 inhibition after ST-elevation myocardial infarction (STEMI) is recommended in clinical guidelines. However, bleeding complications are common, and associated with worse outcomes. The aim of this study was to assess incidence of bleeding events with a clopidogrel-based compared to a ticagrelor-based DAPT strategy, in a real world population. Secondary aims were to assess ischemic complications and mortality. Methods and Results: We identified 330 consecutive STEMI patients with a clopidogrel-based and 330 with a ticagrelor-based DAPT strategy. Patientś medical records were searched for bleeding and ischemic complications, over 6 months follow-up. The two groups were well balanced in baseline characteristics, age (69 years inboth groups), sex (31% vs 32% females), history of diabetes (19% vs 21%), hypertension (43% in both) and MI (17% vs 15%). There was no difference in CRUSADE bleeding score (28 vs 29). After discharge, there were more than twice as many bleeding events with a ticagrelor-based compared with a clopidogrel-based strategy (13.3% vs. 6.5%, p = 0.005). Bleeding events included significantly more severe bleeding complications (TIMI major/minor [5.8 vs 1.0, p = 0.001]) during the ticagrelor-based period. There was no significant difference in the composite of death, MI or stroke (7.8% vs 7.1%, p = 0.76). Conclusions: In this observational study, a ticagrelor-based DAPT strategy was associated with significantly more bleeding complications, without any significant change in death, MI or stroke. Larger studies are needed to determine whether bleeding complications off-sets benefits with a more potent DAPT strategy in older and more comorbid real-life patients.